Bakti untuk Negeri 80 Tahun RI: Pemanfaatan AI untuk Penguatan Kapasitas Ilmiah - arjulayana, Arjulayana; N. Sofianto, Eko Wahyu; Kusumaningsih, Dewi; Halawa, Kerisman; Dayu Rahma Turista, Dora; Diansyah, Tengku Mohd; Baharuddin, Baharuddin; Arifin, Jaenal; Abid, Nuskhan (Keris: Journal of Community Engagement, 2025)
This article describes the community service activities carried out by the Mendeley Advisor Community Indonesia entitled "Service to the Nation 80 Years of the Republic of Indonesia: Utilizing AI to Strengthen Scientific Capacity." This program aims to improve digital literacy and research capacity by artificial intelligence (AI) in an academic context. A total of 230 participants consisting of students, lecturers, and researchers from various provinces took part in this training. The training material covered theoretical and practical aspects of AI use, particularly in literature review, reference management, scientific writing, and research efficiency. Data was collected through pre- and post-training surveys, structured observations, and interviews. The results showed a 70% level of participant satisfaction and engagement, 75%-time efficiency, 85% depth of material, and a 70% increase in practical skills. Although knowledge retention was moderate (60%), this training successfully encouraged the integration of AI into academic practice. Overall, this initiative shows that community-based AI training can strengthen digital competencies and academic productivity, as well as contribute to closing the digital literacy gap in Indonesia.